Deletion of the E3 ubiquitin ligase LRSAM1 fosters intracellular Staphylococcus aureus survival - Ole Plöhn; Abhishek Kumar Singh; Clara Greger; Hannes Wolfgramm; Madina Baglanova; Kristin Surmann; Uwe Völker; Barbara M. Bröker; Karsten Becker; Ulrike Seifert; Clemens Cammann (Frontiers in Cellular and Infection Microbiology)
BackgroundIntracellular invasion and persistence of Staphylococcus aureus can lead to chronic infection and is an effective strategy for the pathogen to evade the host immune response and antibiotic therapy. Selective ubiquitination of bacterial surfaces via E3 ubiquitin ligases is a mechanism by which host cells combat intracellular bacteria and target them for autophagosomal degradation. However, knowledge of the E3 ligases involved in intracellular recognition of S. aureus is still very limited.MethodsWe studied A549 lung epithelial cells during S. aureus infection, focusing on the role of the E3 ligase leucine rich repeat and sterile alpha motif containing 1 (LRSAM1). We used the CRISPR-Cas9 system to generate LRSAM1-deficient A549 cells and monitored intracellular bacterial survival, activation of host cellular signalling pathways related to cytokine production, and host cell death during S. aureus infection.ResultsIn LRSAM1-deficient host cells we observed a significant increase in intracellular bacterial load, which was accompanied by an increased host cell death and elevated secretion of the pro-inflammatory cytokine IL-6. Despite induced selective autophagy, LRSAM1 knockout host cells were incapable of lowering and eliminating the pathogen, which seems to be caused by the reduced ubiquitination of the bacterial surface.ConclusionThe results indicate a significant role of LRSAM1 in the clearance of intracellular S. aureus. This contributes to a deeper understanding of the host cellular responses to S. aureus infection and will facilitate the development of novel therapeutic strategies to combat intracellularly persistent S. aureus.